Cholesterol Lowering Potential of Allium Sativum Essential Oil in Type 2 Diabetic Patients (Medical Forum Monthly, 2020)
Objective: The present study analyzed the cholesterol lowering potential of Allium sativum essential oil (ASEO) in hypercholesterolemia of type 2 Diabetes mellitus (T2DM).Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Faculty of Medicine and Allied Medical Sciences, Isra University Hyderabad from December 2018 to January 2020.Materials and Methods: A sample of 79 diagnosed cases of T2DM was selected according to inclusion and exclusion criteria. 10 ml of venous blood was collected for the analysis of serum total cholesterol, blood glucose, glycated HbA1, BUN and serum creatinine. Ethical clearance of institute and informed consent were mandatory. SPSS 21.0 was used for data analysis at 95% confidence interval.Results: Blood glucose, HbA1c, serum creatinine and blood cholesterol showed significant reductions at third and sixth months compared to baseline. Serum cholesterol at baseline, third and sixth month was noted as 215.2±72.6 mg/dl, 190.7±81.6 mg/dl and 162.8±76 mg/dl respectively (p=0.0001).Conclusion: Allium sativum essential oil reduced hypercholesterolemia in diabetes mellitus. Allium sativum essential oil may prove helpful in treating hypercholesterolemia in diabetic patients as an adjunctive therapy for those intolerant to statin therapy.